Biotechnology, patents and morality a deliberative and participatory paradigm for reform - O'Sullivan, Maureen 1967- (Routledge research in intellectual property, 2020)
This book critiques the decision-making process in Article 53(a) of the European Patent Convention. To date, such decisions have been taken at high levels of expertise without much public involvement. The book eschews traditional solutions, such as those found within legislative, judicial and patent office realms and instead develops a radical blueprint for how these decisions can be put to the public. By examining wide-scale models of participatory democracy and deliberation, this book fills a significant gap in the literature. It will be invaluable for patent lawyers, academics, practitioners and intellectual property and patent officials